Development and In Vitro Evaluation of an Innovative "Dietary Flavonoid Supplement" on Osteoarthritis Process. (7th March 2017) - Lauro, Maria Rosaria; Crascí, Lucia; Sansone, Francesca; Cardile, Venera; Panico, Anna Maria; Puglisi, Giovanni
Abstract : The aim of this study was to evaluate the antidegenerative effect in osteoarthritis damage of eriocitrin alone and eriocitrin formulated as innovative "dietary flavonoid supplement." A complexation between eriocitrin and hydroxypropyl β -cyclodextrin by solubilization/freeze-drying method was performed. The complex in solution was evaluated by phase solubility studies and the optimal 1 : 2 flavanone/cyclodextrin molar ratio was selected. Hydroxypropyl β -cyclodextrin was able to complex eriocitrin as confirmed by UV-Vis absorption, DSC, and FTIR studies. The complex formed increased the eriocitrin water solubility (from 4.1 ± 0.2  g·L −1 to 11.0 ± 0.1  g·L −1 ) and dissolution rate (from 37.0% to 100%) in 30 min. The in vitro studies exhibit the notion that eriocitrin and its complex inhibit AGEs in a similar manner because hydroxypropyl β -cyclodextrin does not interfere with the flavanone intrinsic property. Instead, the presence of cyclodextrin improves eriocitrin antioxidant stability maintaining a high fluorescence value until 8 hours with respect to the pure materials. Moreover, hydroxypropyl β -cyclodextrin showed moderate GAGs restoration acting synergistically with the complexed compound to maintain the structural chondrocytes integrity. The results point out that ERT/HP-betaCD complex possesses technological and biological characteristics able to obtain an easily soluble nutraceutical product, which reduces the degenerative and oxidative damage which occurs in osteoarthritis, and improve the patient compliance.